Selection of tomato accessions resistant to Verticilium wilt - Renato Carrer Filho; Renata Maria Oliveira; Vanessa Duarte Dias; Geisiane Alves Rocha; Érico de Campos Dianese; Marcos Gomes da Cunha (Pesquisa Agropecuária Tropical, 2016)
Vascular wilting in tomato plants is an important disease caused by soil-inhabiting pathogens, especially Verticillium dahliae, which results in significant production losses. Control measures against this disease are difficult to implement due to intrinsic pathogen characteristics, such as high adaptability to the subterranean environment, in association with the host, and development of resistance structures that remain viable in the soil for long periods. The introgression of genes that express resistance is the main control measure and requires a continuous characterization program of resistant accessions. This study aimed at identifying tomato (Solanum lycopersicum) accessions resistant to V. dahlia, by using the phenotypic and genotypic methods. The reaction of 33 tomato accessions to different V. dahliae isolates was reinforced by molecular analysis, through markers linked to Ve resistance genes. The combination of bioassays and specific molecular markers showed a high correlation (94.3 %), with the selection of 25 accessions resistant to V. dahliae.